Response of soil strength and density to compost application: A study on the vegetative phase of pineapple - Dermiyati, Dermiyati; Rahmawanty, Adisty; Afandi, Afandi; Larasati, Jeni; Ramadhani, Winih Sekaringtyas; Yuwono, Slamet Budi (Journal of Degraded and Mining Lands Management, 2026)
This study aimed to determine the effects of applying 50 t ha?¹ of compost, made from a mixture of cow dung, bromelain waste, and chopped bamboo, on soil compaction and penetration in pineapple (Ananas comosus L. Merr.) plantations in Central Lampung, Indonesia. This study used a survey method at four locations, each representing a different age of pineapple plants. Soil penetration analysis was performed using a Digital Cone Penetrometer. Soil bulk density and total pore space were determined using the volumetric method. The results indicated that soil compaction decreased with increasing pineapple plant age, corresponding to a reduction in soil bulk density. Specifically, the soil bulk density values for pineapple plants at 0, 3, 5, and 9 months after planting (MAP) were 1.42 g cm?³, 1.23 g cm?³, 1.13 7 g cm?³, and 1.02 g cm?³, respectively. Lower soil bulk density corresponded to less soil compaction, leading to lower soil penetration resistance. The lowest soil penetration value was recorded at location 9 MAP, while other locations remained below the critical soil penetration limit. A lower soil penetration value indicates reduced soil strength. There was a positive correlation between soil bulk density and specific gravity, and between soil penetration and age at 5 and 9 months. Conversely, higher soil pore space and dispersion index were associated with decreased soil penetration. In conclusion, applying 50 t ha?¹ of compost appears to be an effective solution for pineapple cultivation.